Genome‐wide screening of potential RNase Y‐processed mRNAs in the M49 serotype Streptococcus pyogenes NZ131. Issue 4 (13th June 2018) - Chen, Zhiyun; Raghavan, Rahul; Qi, Fengxia; Merritt, Justin; Kreth, Jens
Abstract: RNase Y is a major endoribonuclease in Group A streptococcus (GAS) and other Gram‐positive bacteria. Our previous study showed that RNase Y was involved in mRNA degradation and processing in GAS. We hypothesized that mRNA processing regulated the expression of important GAS virulence factors via altering their mRNA stabilities and that RNase Y mediated at least some of the mRNA‐processing events. The aims of this study were to (1) identify mRNAs that were processed by RNase Y and (2) confirm the mRNA‐processing events. The transcriptomes of Streptococcus pyogenes NZ131 wild type and its RNase Y mutant ( Δrny ) were examined with RNA‐seq. The data were further analyzed to define GAS operons. The mRNA stabilities of the wild type and Δrny at subgene level were determined with tiling array analysis. Operons displaying segmental stability in the wild type but not in the Δrny were predicted to be RNase Y processed. Overall 865 operons were defined and their boundaries predicted. Further analysis narrowed down 15 mRNAs potentially processed by RNase Y. A selection of four candidates including folC1 (folylpolyglutamate synthetase), prtF (fibronectin‐binding protein), speG (streptococcal exotoxin G), ropB (transcriptional regulator of speB ), and ypaA (riboflavin transporter) mRNAs was examined with Northern blot analysis. However, only folC1 was confirmed to be processed, but it is unlikely that RNase Y is responsible. We conclude that GAS use RNase Y to selectively process mRNA, but the overall impact is confined to selected virulence factors. Abstract : Streptococcus pyogenes or group A Streptococcus (GAS) is a significant human pathogen. GAS causes a variety of disease ranging from uncomplicated pharyngitis to life‐threatening invasive infections. The genetic control of virulence factors required for disease manifestation has been well documented, but posttranscriptional regulatory mechanisms have not been fully understood. The endoribonuclease RNase Y is responsible for bulk RNA turnover in GAS but also processes RNA increasing the stability of certain transcripts. Here, we aimed to identify RNase Y‐processed transcripts in GAS on a global scale to better understand the role of posttranscriptional regulation in S. pyogenes virulence.